2010
DOI: 10.1167/iovs.09-4573
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for Carbachol-Induced Secretion of Lacritin in Cultured Monkey Lacrimal Acinar Cells

Abstract: Successful culture of monkey lacrimal acinar cells showed that, among the prevalent tear proteins, the secretion of lacritin involved the PKC/Ca2+ pathway, not the p42/p44 MAPK pathway. Induction of transcription by Cch involved the independent p42/p44 MAPK and PKC pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
1
8
1
Order By: Relevance
“…In rat LG, Cch-induced phosphorylation of p42/44 inhibits secretion [5,17]. In monkey LG, the Cch-induced secretion was found to be independent of p42/44 [16]. The results presented here showed no statistically significant p42/44 phosphorylation by Cch stimulation, even if phosphorylation was observed in some samples.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…In rat LG, Cch-induced phosphorylation of p42/44 inhibits secretion [5,17]. In monkey LG, the Cch-induced secretion was found to be independent of p42/44 [16]. The results presented here showed no statistically significant p42/44 phosphorylation by Cch stimulation, even if phosphorylation was observed in some samples.…”
Section: Discussioncontrasting
confidence: 50%
“…1). Several studies have been performed investigating the role of MAPKs in lacrimal secretion, most of them regarding p42/44 [5,[15][16][17], but also c-Jun N-terminal kinase (JNK) [14]. In rat LG, Cch-induced phosphorylation of p42/44 inhibits secretion [5,17].…”
Section: Discussionmentioning
confidence: 99%
“…The cholinergic system plays an important role in fluid and electrolyte transport in epithelia. For example, mAChR agonists and antagonists are commonly used to treat impaired saliva and tear secretion (Melvin et al, 2005;Morimoto-Tochigi et al, 2010). However, it is noteworthy that material transport across epithelial cells can be accomplished by either transcellular or paracellular pathways (Tsukita et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…9 For example, in cultured monkey lacrimal acinar cells, we previously reported that acetylcholine analog carbachol (Cch) increased intracellular Ca 2þ , activated the protein kinase C (PKC) pathway, and promoted secretion of the tear protein lacritin. 10 Lacritin protein expression has been detected in primates, and high expression was found in human lacrimal and meibomian glands. 11 Recently, lacritin expression was also found in nonprimate horse tears.…”
mentioning
confidence: 99%
“…13 Cholinergic stimulation induced secretion of lacritin from monkey lacrimal acinar cells, suggesting that lacritin is produced in the lacrimal gland and is secreted onto the ocular surface. 10 Since a decrease of tear lacritin was reported in patients with blepharitis 14 and in contact lens-related dry eye, 15 lacritin might play an important role in maintaining tear fluid and the ocular surface. Indeed, lacritin promoted protein secretion from cultured rat acinar cells 16 and stimulated proliferation in cultured human corneal cells and salivary ductal cells.…”
mentioning
confidence: 99%